Gestational choriocarcinoma at Juba Medical Complex and Juba Teaching Hospital: five case reports - Kizza Paul; Kuma Chuol Biel; Anthony Lupai; Mirghany Abdallah; Changkel Banak; Paula Nuer (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2019)
Gestational choriocarcinoma (GCC) is the most malignant of the four gestational trophoblastic diseases. The others are: invasive mole, placental site trophoblastic tumour, and epithelioid trophoblastic tumour. We report five cases of GCC managed at the Juba Medical Complex and Juba Teaching Hospital since 2011. The purpose is to draw attention to this condition with its complex presentations, need for early diagnosis and potential for cure. Recurrent vaginal bleeding in the presence of a pregnancy of unknown location and a positive pregnancy test should make the clinician suspect GCC. A woman of childbearing age with disseminated malignancy of unknown primary cause should have a pregnancy test.